Effects of direct acting antiviral therapy on liver stiffness measured by using fibro scan in Egyptian patients with chronic hepatitis C - Abdel Gadallah Naser Abdel Atty; Abdullah Bahnasi Abdulaziz; Waleed Abdelfattah; Mousa Dr; Mohammed Elsayaad Shafiek Mohammed; Hany Elbasyouni Abdelbary Abdelaziz (Medicinski glasnik, 2023)
Aim: Egypt has the highest incidence of hepatitis C virus (HCV) infection in the world. Fibrosis development is common in HCV cases, and it is important in disease prediction. The aim of this study was to demonstrate the role of fibro scan in assessment of changes in hepatic stiffness in patients with chronic HCV infection following direct acting antiviral treatment (DAAT). Methods: This prospective observational research included 120 patients with compensated HCV infection. All patients were subjected to fibro scan before and after receiving DAAT. Patients’ history, clinical examination, laboratory parameters (red - RBCs, and white blood cells - WBCs, hepatic function test, renal function test, coagulation profile, HBsAg, AFP - alpha feto protein, HbA1C, HCVAb) and fibro scan were done for all patients. Results: Stiffness may differentiate F0-2 minimal fibrosis from F3-4 massive fibrosis using ROC-curve analysis, with 77.5% sensitivity, 90% specificity, 88.57% positive predictive value (PPV), and 80% negative predictive value (NPV). With sensitivity, specificity, PPV, and NPV of 71.4%, 44.5%, 43.48%, and 71.43%, respectively, the APRI-score can discriminate F0-2 from F3-4 at cutoff of 0.314. At a cutoff of 1.18, Fib4 calculation can discriminate F0-2 from F3-4, with sensitivity, specificity, PPV, and NPV of 78.6%, 64.1%, 63.04%, and 78.57%, respectively. Conclusion: Hepatic fibrosis measurements such as fibro scan and non-invasive fibrosis scores (FIB-4) and aspartate aminotransferase (AST) to platelet ratio index (APRI) showed a significant improvement after direct-acting antiviral therapy. Improvements in hepatic function tests, serum creatinine level, and platelet count are also seen.
Keywords: HCV; hepatic fibrosis progression; liver stiffness